1999
DOI: 10.1002/(sici)1097-0223(199912)19:12<1143::aid-pd730>3.3.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a de novo complex chromosome rearrangement involving chromosomes 4, 11, 12 and 13 and eight breakpoints by conventional cytogenetic, fluorescence in situ hybridization and spectral karyotyping

Abstract: A complex chromosome rearrangement (CCR) with eight breakpoints resulting in four derivative chromosomes (4, 11, 12 and 13) was detected prenatally in a male fetus of a twin pregnancy. The karyotype of the female second fetus was normal. The apparently balanced de novo CCR was identified by classical cytogenetic methods and fluorescence in situ hybridization (FISH). We compared these findings with results from spectral karyotyping (SKY).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 21 publications
1
11
0
1
Order By: Relevance
“…The occurrence of complex chromosomal rearrangements is believed to be relatively rare. However, a growing number of complex chromosomal rearrangements have been reported (Madan et al 1997;Peschka et al 1999;Callen et al 2002) in which more breaks than expected have been observed. As the rearrangements become more complicated, with more and more breaks, the risk for associated abnormalities increases (Madan et al 1997).…”
Section: Introductionsupporting
confidence: 73%
“…The occurrence of complex chromosomal rearrangements is believed to be relatively rare. However, a growing number of complex chromosomal rearrangements have been reported (Madan et al 1997;Peschka et al 1999;Callen et al 2002) in which more breaks than expected have been observed. As the rearrangements become more complicated, with more and more breaks, the risk for associated abnormalities increases (Madan et al 1997).…”
Section: Introductionsupporting
confidence: 73%
“…When CCR is reevaluated by using advanced techniques, the number of breakpoints tends to increase over the number that initially was identified by using conventional cytogenetic techniques (22,23). The carriers of CCRs may transmit a balanced or unbalanced karyotype to offspring in the family (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Constitutional complex chromosome rearrangements (CCRs) are usually ascertained postnatally in patients with congenital malformations and mental retardation/ developmental delay [Joyce et al, 1999], or in normal carriers with a history of pregnancy losses, infertility, or offspring with an unbalanced karyotype [Rothlisberger et al, 1999]. Prenatal cases detected in fetuses with malformations or through studies due to advanced maternal age or abnormal levels of biochemical markers in maternal serum are less frequent [Peschka et al, 1999].…”
Section: Introductionmentioning
confidence: 99%